2011
DOI: 10.3109/10641963.2011.577485
|View full text |Cite
|
Sign up to set email alerts
|

Serum Gamma-Glutamyl Transferase (GGT) Levels and Inflammatory Activity in Patients With Non-dipper Hypertension

Abstract: Non-dipper hypertension is associated with increased cardiovascular morbidity and mortality. We aimed to evaluate serum gamma-glutamyl transferase (GGT) level, which is accepted as a marker for oxidative stress and its relationship with inflammatory activity in patients with non-dipper hypertension. Age and sex matched 43 dipper hypertensive patients, 40 non-dipper patients, and 46 healthy subjects were included into the study. Serum GGT and C-reactive protein (CRP) levels were measured and compared between ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Mean platelet volume, which is a determinant of platelet activation, was higher among nondippers compared to dippers (9.72 ± 0.52 fL versus 9.38 ± 0.33 fL, P < 0.05) 18. Inflammatory markers, such as c-reactive protein, were also higher among nondippers 18,19…”
Section: Association Of Nondippers With Risk Factors and Target Organmentioning
confidence: 88%
“…Mean platelet volume, which is a determinant of platelet activation, was higher among nondippers compared to dippers (9.72 ± 0.52 fL versus 9.38 ± 0.33 fL, P < 0.05) 18. Inflammatory markers, such as c-reactive protein, were also higher among nondippers 18,19…”
Section: Association Of Nondippers With Risk Factors and Target Organmentioning
confidence: 88%
“…The nondipper pattern is associated with an increased risk for cardiovascular, cerebrovascular, and renal complications 4,5,41 . Although the exact mechanisms of nondipping pattern have yet to be wholly elucidated, studies suggest that nondippers display impaired autonomic dysfunction, higher sympathetic activity, and higher inflammatory activity 42–45 . While the relationship between UA and hypertension is not debated, 36 currently there is no information on whether UA is related to nondipper status in essential hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,41 Although the exact mechanisms of nondipping pattern have yet to be wholly elucidated, studies suggest that nondippers display impaired autonomic dysfunction, higher sympathetic activity, and higher inflammatory activity. [42][43][44][45] While the relationship between UA and hypertension is not debated, 36 currently there is no information on whether UA is related to nondipper status in essential hypertension. In our study, increased serum UA was an independent and strong predictor of nondipper hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that nondippers display impaired autonomic dysfunction (17), higher sympathetic activity (18), higher inflammatory activity (19,20), prominent insulin resistance (2) and increased oxidative stress leading to endothelium-dependent vasodilation dysfunction (21). Clinical observations have shown the association of several plasma biomarkers with nondipper hypertension, including plasma atrial and brain natriuretic peptides (22) and vitamin D deficiency (23).…”
Section: Discussionmentioning
confidence: 99%